Screening of cognitive dysfunction in outpatients with major depressive disorder and its associated factors in Hospital Selayang / Husni Zaim Ab Latiff - Ab Latiff, Husni Zaim (2019)
Background: Major Depressive Disorder (MDD) is a significant mental health problem worldwide. Cognitive dysfunction (CD) is frequently observed both during acute episode and as residual symptom of MDD. It as a predominant symptom of MDD, contributing to impairment of social and occupational functioning. Objective: General objective of this study was to assess and describe CD amongst adult patients with MDD under psychiatric clinic follow up at Hospital Selayang. Specific objectives were to determine the prevalence of CD among MDD in study population, to compare the sociodemographic and clinical profiles, to determine the domains of cognition mostly affected and the factor(s) associated with CD among study population. Methodology: This was a cross-sectional study involving MDD patients attending psychiatric clinic in Hospital Selayang, who were recruited through systematic random sampling. Those who fulfilled the selection criteria and gave informed consent were selected. Sociodemographic data was obtained from the patients. Clinical data was obtained from clinical notes. Confirmation of MDD was done using Mini International Neuropsychiatric Interview (M.I.N.I 7.0). Screening for CD was done using Montreal Cognitive Assessment (MoCA). Descriptive analysis was performed, followed by univariate analysis and multiple logistic regression analysis. Results: Of the total 245 participants, 32.7% (n=80, 95% CI: 26.7, 38.6) patients with MDD had CD. From multiple logistic regression, presence of CD amongst MDD patient was significantly associated with secondary education level and lower (OR: 6.09; 95% CI: 2.82, 13.16; p<0.001), five or more depressive episodes (OR: 8.93; 95% CI: 3.24, 24.67; p<0.001), treatment non-compliance (OR: 3.48; 95% CI: 1.40, 6.59; p=0.003), and presence of medical comorbidity (OR: 2.74; 95% CI: 1.46, 5.18; p=0.002). Conclusion: CD is prevalent among patients with MDD in Hospital Selayang. Having low education level, five or more episodes of depression, treatment non-compliance, and medical comorbidity strongly associated to CD amongst MDD patients. Hence, clinician need to be cognisant of CD and its associated factors in the treatment of the MDD patients. Its routine assessment possibly warranted in clinical setting.